Re-establishment of Malletia sorror (Soot-Ryen, 1957), an endemic bathyal bivalve off Chile (Mollusca: Bivalvia: Nuculanoidea) - Michael L. Zettler (Gayana)
Fresh material of a nuculanoid bivalve of the genus Malletia, collected during an expedition of the R/V SONNE off Chile in 2023, allows the re-establishment of Malletia sorror (Soot-Ryen, 1957), a species previously considered a synonym of M. peruviana Dall, 1908. The morphology and anatomy of the new material is described and the characteristics that justify a separation from M. peruviana Dall, 1908 are worked out.